Globalization and culture global mélange - Nederveen Pieterse, Jan (Lanham, Maryland Rowman & Littlefield, 2015)
"Now in a fully revised and updated edition, this seminal text disputes the view that we are experiencing a "clash of civilizations" as well as the idea that globalization leads to cultural homogenization. Instead, Jan Nederveen Pieterse argues that we are witnessing the formation of a global mélange culture through processes of cultural mixing or hybridization. From this perspective on globalization, conflict may be mitigated and identity preserved, albeit transformed. In a new chapter on China, the author focuses on the key issue of agency and power in hybridization, which is important in emerging economies generally, with China a particularly momentous case. Here he draws a key distinction between passive and active forms of globalization (globalized and globalizing) and hybridity (being hybridized and hybridizing). Throughout, the book offers a comprehensive treatment of hybridization arguments, and, in discussing globalization and culture, unbundles the meaning of culture. This historically deep and geographically wide approach to globalization is essential reading as we face the increasing spread of conflicts bred by cultural misunderstanding"--Publisher's description.
Globalization : consensus and controversies -- Globalization and human integration : we are all migrants -- Globalization and culture : three paradigms -- Globalization as hybridization -- Hybridity, so what? the anti-hybridity backlash and the riddles of recognition -- Globalization is braided : East-West osmosis -- Hybrid China -- Global mélange.
Includes bibliographical references (pages 183-210) and index.
Keywords: Globalization; Globalization -- Moral and ethical aspects; Globalization -- Political aspects; Acculturation; Popular culture